Simultaneous In Vivo Time Course and Dose Response Evaluation for TCDD-Induced Impairment of the LPS-stimulated Primary IgM Response - North, Colin M. (Oxford University Press, 2009)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a potent suppressor of humoral immunity but the specific molecular mechanisms responsible for immunosuppression by TCDD are poorly understood. In vivo and in vitro studies of the primary humoral IgM response demonstrated that the B cell is a sensitive cell type to modulation by TCDD. We hypothesized that in vivo administration of TCDD disrupts expression of transcription factors controlling B cell to plasma cell differentiation. Female C57BL6 mice were treated with a single dose of TCDD (3, 10, or 30 μg/kg) and/or vehicle (sesame oil). On day 4 post-TCDD administration mice were sensitized with 25 μg lipopolysacchride (LPS) by intraperitioneal injection to stimulate an immune response. Splenocytes were isolated on subsequent days following LPS, up to 3 days post-LPS, and the expression of IgM, XBP-1, PAX5, BCL-6, and Blimp-1 was assessed. TCDD treatment dose-dependently suppressed LPS-induced IgM antibody-forming cell number, which was correlated with decreased frequency of CD19(+) CD138(+) cells. Gene expression analysis revealed that TCDD caused a dose-dependent suppression of Igμ chain, Igκ chain, IgJ chain, XBP-1, and Blimp-1. TCDD also dose-dependently suppressed LPS-stimulated increases in Blimp-1 protein expression in CD19(+) B cells. The deregulation of Blimp-1 expression by TCDD provides a partial explanation for the concomitant suppression of the IgM response and confirms previous observations established in vitro.